Diffrential equation is
"\\cos^2(y)dx+(1+e^{-x})\\sin(y)dy=0"Now, divide the above equation by "\\cos^2(y)(1+e^{-x})" ,thus
"\\frac{dx}{1+e^{-x}}+\\frac{\\sin(y)}{\\cos^2(y)}dy=0\\\\\n\\implies \\frac{e^x}{1+e^x}dx+\\frac{\\sin(y)}{\\cos^2(y)}dy=0\\\\\n\\implies \\int\\frac{e^x}{1+e^x}dx+\\int\\frac{\\sin(y)}{\\cos^2(y)}dy=\\text{constant}\\\\\n\\implies \\ln(1+e^x)-\\int\\frac{1}{u^2}du=\\text{constant, where $u=\\cos(y)$}\\\\\n\\implies \\textcolor{blue}{\\ln(1+e^x)+\\frac{1}{\\cos(y)}}=\\text{\\textcolor{blue}{constant}}"
Comments
Leave a comment